1998
DOI: 10.1176/jnp.10.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Mild Traumatic Brain Injury in Combat Veterans With PTSD and a History of Blast Concussion

Abstract: Veterans with chronic posttraumatic stress disorder were evaluated for a history of blast concussion, controlling for confounding conditions. Electroencephalograms were analyzed by discriminant function for traumatic brain injury. A difference was found in discriminant scores between veterans with and without blast concussion. More members of the blast group had attentional symptoms and attentional dysfunction. Combat veterans with a remote history of blast injury have persistent electroencephalographic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 14 publications
2
91
0
1
Order By: Relevance
“…4,8,[12][13][14][15] Furthermore, patients might also be receiving a number of additional treatments at the same time as biofeedback, such as medications, cognitive rehabilitation therapies, physical therapy, and general psychotherapy, as well as potentially experiencing ongoing or ''spontaneous'' recovery over the time following the injury, in addition to having comorbid diagnoses or symptoms that mimic those associated with TBI (e.g., attention-deficit hyperactivity disorder or PTSD). 1,7,8,[12][13][14]16 216 GRAY Therefore, the heterogeneity related to both the injury and to biofeedback as a treatment can add to challenges in making conclusions about the efficacy of this approach from the research literature, and there needs to be more blinded, randomized, controlled trials with identified protocols using biofeedback for the treatment of symptoms of TBI in both civilian and military populations. 4 However, in a review of research on the efficacy of biofeedback in general for various medical conditions, TBI was listed as having a ''Level 3; Probably Efficacious'' efficacy rating on an Association for Applied Psychophysiology and Biofeedback scale that spanned from Level 1 (''Not empirically supported'') to Level 5 (''Efficacious and specific).…”
Section: Biofeedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…4,8,[12][13][14][15] Furthermore, patients might also be receiving a number of additional treatments at the same time as biofeedback, such as medications, cognitive rehabilitation therapies, physical therapy, and general psychotherapy, as well as potentially experiencing ongoing or ''spontaneous'' recovery over the time following the injury, in addition to having comorbid diagnoses or symptoms that mimic those associated with TBI (e.g., attention-deficit hyperactivity disorder or PTSD). 1,7,8,[12][13][14]16 216 GRAY Therefore, the heterogeneity related to both the injury and to biofeedback as a treatment can add to challenges in making conclusions about the efficacy of this approach from the research literature, and there needs to be more blinded, randomized, controlled trials with identified protocols using biofeedback for the treatment of symptoms of TBI in both civilian and military populations. 4 However, in a review of research on the efficacy of biofeedback in general for various medical conditions, TBI was listed as having a ''Level 3; Probably Efficacious'' efficacy rating on an Association for Applied Psychophysiology and Biofeedback scale that spanned from Level 1 (''Not empirically supported'') to Level 5 (''Efficacious and specific).…”
Section: Biofeedbackmentioning
confidence: 99%
“…4,12,18,[27][28][29] EEG patterns have been shown to be different in individuals following TBI, and have even been shown to predict prognosis in some cases. 7,12,26,27 Sideeffects from neurofeedback can include headaches, nausea, dizziness, fatigue, and agitation. 18 These are common symptoms that TBI survivors seek to mitigate that might be worsened by the use of a computer screen to provide feedback, which can exacerbate symptoms in some patients with brain injuries.…”
Section: Neurofeedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-morbid attention deficit disorder and a recall bias of previous head injury could have impacted the study results. 24 Outcome or disability was not correlated to coherence measurements.…”
Section: Time-independent Qeeg Changes In Mtbimentioning
confidence: 92%
“…24 Interestingly, however, although the discriminant scores could differentiate between a history of self-recollected blast injury, it could not reliably detect those with a history of other TBI or mTBI. This study also suffered from small sample sizes and was self-described as ''exploratory.''…”
Section: Time-independent Qeeg Changes In Mtbimentioning
confidence: 96%